2016
DOI: 10.1186/s12888-016-1130-0
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte disorders and aging: risk factors for delirium in patients undergoing orthopedic surgeries

Abstract: BackgroundAt present, the exact mechanism of postoperative delirium has not been elucidated. The purpose of this study was to analyze the incidence of delirium in patients undergoing orthopedic surgeries and to explore possible related factors.MethodsThis is a retrospective study. We used 582 patients who had undergone orthopedic surgery between January 2011 and December 2014. The surgeries consisted of 155 cases of internal fixation for intertrochanteric fracture (IFIF), 128 cases of femoral head replacement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
53
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 30 publications
(44 reference statements)
15
53
1
Order By: Relevance
“…In terms of demographics, patients suffered from postoperative delirium were significantly older than those without. This was highly consistent with previous studies which had identified advanced age as a common independent predictor of postoperative delirium [1,9,20,21,22,23,24,25].Interestingly, there was significant difference of race distribution between the two groups, indicating a racial difference in occurrence of postoperative delirium. Our study found that the Whites occupying a larger proportion in the postoperative delirium group.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In terms of demographics, patients suffered from postoperative delirium were significantly older than those without. This was highly consistent with previous studies which had identified advanced age as a common independent predictor of postoperative delirium [1,9,20,21,22,23,24,25].Interestingly, there was significant difference of race distribution between the two groups, indicating a racial difference in occurrence of postoperative delirium. Our study found that the Whites occupying a larger proportion in the postoperative delirium group.…”
Section: Discussionsupporting
confidence: 91%
“…In order to optimize postoperative outcomes and prevent complications, it is critical to identify preoperatively whether patients are at high risk of postoperative delirium [1,19,20,21]. Several risk factors of postoperative delirium had been reported in previous literatures, among which advanced age is the most frequently acknowledged [1,9,19,20,21,22,23,24,25]. Other risk factors, including a history of dementia or psychiatric illness, cognitive impairment, polypharmacy, postoperative electrolyte disorders, and diabetes, had also been identified [1,9,20,21,22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intravenous zoledronic acid and subcutaneous denosumab and romosozumab are associated with hypocalcemia, (20,73,74) for example, which is a significant risk factor for postoperative delirium in patients undergoing hip fracture repair. (75) These drugs are contraindicated in patients with hypocalcemia, (74,76,77) and many surgical patients are hypocalcemic in the postoperative period. (78)(79)(80) In the key HORIZON Recurrent Fracture Trial, patients with osteoporosis who had recently fractured a hip did not receive their first zoledronic acid infusion until after they had taken calcium and vitamin D supplements for at least 2 weeks.…”
Section: Recommendationmentioning
confidence: 99%
“…There is no mention about the preoperative functional status of patients and history of any psychiatric disorder including depression, 2 independent predictors of POD reported in a systematic review of patients undergoing total joint arthroplasty [3]. Moreover, there is no information about postoperative laboratory parameters including postoperative day 3 blood urea nitrogen, serum electrolytes, and fluid balance, which could have potentially influenced the delirium incidence in the 2 groups [4,5]. Also, postoperative rehabilitation protocol, including the mobility status of the patients, which could have affected the development of delirium, should have been discussed in the 2 groups.…”
Section: To the Editormentioning
confidence: 99%